CODE SWITCHING DI LOKASI KERJA PT. IWIP; STRATEGI KOMUNIKASI DALAM LINGKUNGAN MULTIBAHASA - latif ajas tihurua (Hunatech Vol. XXX, No. XXX, 2025)
The multilingual work environment at PT Indonesia Weda Bay Industrial Park (PT. IWIP) demands effective communication strategies for efficient interaction between employees. One of the strategies used is Code-Switching, which is the alternation of languages in a single conversation. This investigation aims to analyze the benefits, challenges, and strategies of using Code-Switching in the workplace of PT. IWIP. The study method used was a qualitative approach with observations and interviews of employees working in a multilingual environment. The results showed that Code-Switching can improve communication effectiveness, bridge cultural differences, and create a more inclusive work environment. However, challenges such as misunderstandings and lack of standardization of communication still need to be addressed. With proper implementation, Code-Switching can be a communication tool that supports productivity and work efficiency at PT. IWIP.